'We Are Here Alone': The Ironic Potentials and Vulnerabilities of Mixed (Up) Districts in Central Jakarta. (8th July 2013) - Simone, Abdoumaliq
Abstract The durability of central city districts in large metropolitan systems of the majority world has largely been attained through intricate intersections of physical, infrastructural, human and discursive materials, as these intersections are continuously remade through shifting constellations of the incremental initiatives of residents. Residents have learned to use the city as a place to continuously explore new relationships among things and extract a wide range of unanticipated capacities from them. This is a collective resourcefulness from which there might be much to draw in terms of using the carbon‐driven exigencies of infrastructural transformation as the occasion to reanimate more egalitarian political projects. Although many collective efforts are increasingly being disassembled, the reflections of a single resident of one of Jakarta's most heterogeneous residential districts points to how the revitalization of such efforts might be conceived. The efficacy of political efforts to address intensified vulnerability partly entails replenishing intense mixtures of built and physical environments as provocations and platforms for complex social maneuvers.